The Military History of the Soviet Union
VIII, 328 p.
Keywords: The Military History of the Soviet Union and The Military History of Tsarist Russia treat Russian military history from the rise of the Muscovite state to the present, even peeking briefly into the future. The two volumes will cover Russia's land forces extensively, but will also cover the development of the Russian Navy, and the creation and development of the Russian Air Force, parts of the Russian military machine which are frequently neglected in general writings. The historical analysis will address the development and function of the Russian military whether in peace or in war, as well as the impact of war and changes in the military upon Russian society and politics.